Contesting the Fitrah: Negotiating Childfree Choices and Islamic Motherhood in the Digital Sphere - Citra Imro’atun Najwa Wijaya (Zamzami Scholar Publishing, 2026)
The phenomenon of childfree is becoming increasingly popular in the digital space and has sparked debates that reflect changes in social values, gender identity, and religious dynamics among Muslim women. Childfree is no longer understood as merely a personal decision, but as a social issue that challenges procreation norms and traditional views on the role of women in reproduction. This study aims to analyze how the representation and negotiation of the meaning of ‘childfree’ are formed through digital interactions, using a qualitative method based on netnography, which involves observing video content and comments on the YouTube channel @MenjadiManusia. The results of the study show that digital space is an important arena for the emergence of alternative voices, especially from women who negotiate their rights over their bodies and personal autonomy, while those who reject childfree use arguments of religion and Muslim family morality as the basis for their criticism. These findings align with Heidi A. Campbell’s theory, which posits that digital spaces foster the formation of new identities and authorities as religious values are negotiated through online interactions. Thus, the representation of childfree reflects a shift in the way Muslim societies interpret family, gender roles, and reproductive decisions, and contributes to strengthening digital literacy and efforts to reduce gender-based stigma.